2016
DOI: 10.1074/jbc.m115.677930
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 1 (HDAC1) Negatively Regulates Thermogenic Program in Brown Adipocytes via Coordinated Regulation of Histone H3 Lysine 27 (H3K27) Deacetylation and Methylation

Abstract: Inhibiting class I histone deacetylases (HDACs) increases energy expenditure, reduces adiposity, and improves insulin sensitivity in obese mice. However, the precise mechanism is poorly understood. Here, we demonstrate that HDAC1 is a negative regulator of the brown adipocyte thermogenic program. The Hdac1 level is lower in mouse brown fat (BAT) than white fat, is suppressed in mouse BAT during cold exposure or ␤ 3 -adrenergic stimulation, and is down-regulated during brown adipocyte differentiation. Remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 65 publications
3
106
0
Order By: Relevance
“…Adipose-selective transgenic expression of FOXC2 increases intracellular cAMP levels by increasing the expression of PKA (the RIα subunit) and promotes beige adipocyte thermogenesis in WAT 62 . By contrast, histone deacetylase HDAC1 (and HDAC2) inhibits thermogenesis through deacetylation of H3K27 on the regulatory regions of Ucp1 , which then inhibits CREB and ATF2 mediated transcription 74 . Intriguingly it has been recently found that casein kinase 2 (CK2) activity in response to β-AR signalling is preferentially increased in WAT and inhibits the thermogenic programme in this tissue.…”
Section: Regulation Of Adipocyte Thermogenesismentioning
confidence: 99%
“…Adipose-selective transgenic expression of FOXC2 increases intracellular cAMP levels by increasing the expression of PKA (the RIα subunit) and promotes beige adipocyte thermogenesis in WAT 62 . By contrast, histone deacetylase HDAC1 (and HDAC2) inhibits thermogenesis through deacetylation of H3K27 on the regulatory regions of Ucp1 , which then inhibits CREB and ATF2 mediated transcription 74 . Intriguingly it has been recently found that casein kinase 2 (CK2) activity in response to β-AR signalling is preferentially increased in WAT and inhibits the thermogenic programme in this tissue.…”
Section: Regulation Of Adipocyte Thermogenesismentioning
confidence: 99%
“…LSD1 is recruited to brown/beige adipogenic enhancers through its interactions with transcription factors Nrf1 and Zfp516 (71, 267). Cold exposure decreases histone deacetylase 1 (Hdac1) levels in BAT, and β adrenergic signaling decreases the binding of Hdac1 to the UCP1 and PGC1α promoters in brown adipocytes, leading to an increase in active epigenetic H3K27ac mark (181). Concurrently, β adrenergic signaling stimulates dissociation of enhancer of zeste homologue (Ezh2) and suppressor of zeste 12 (SUZ12), leading to a decrease in repressive epigenetic mark H3K27me3 at the UCP1 and PGC1α promoters (181).…”
Section: Genetic and Epigenetic Regulation Of Brown And Beige Fat Thementioning
confidence: 99%
“…The favourable open chromatin structure for Ucp1 transcriptional activation after β-AR stimulation has been previously reported in cultured brown adipocyte, demonstrated by a significant increase of H3K27ac in both the Ucp1 and Pgc1α promoter regions [12]. However, which factors regulate behind this phenomenon is still unclear.…”
Section: Discussionmentioning
confidence: 93%